Rooting as indicator of wild boar density: environmental drivers and spatial variation across protected areas - Martina Calosi; Niccolò Fattorini; Rosa Maria Di Biase; Agnese Marcelli; Caterina Pisani; Chiara Gabbrielli; Sonia Aleotti; Mattia Galdangelo; Francesco Ferretti (Ecological Indicators, 2025)
Wild ungulates play crucial roles in food webs and their impacts can propagate across trophic levels. The recent spread of wild boar Sus scrofa is generating concerns worldwide for its potential negative impacts on biodiversity and human activities. Under particular conditions, its foraging activity through digging the topsoil (i.e., rooting) may affect endangered plant/animal species or agriculture. Identifying environmental drivers of rooting is crucial to address spatially-explicit measures to reduce negative impacts, as well as to clarify the often unclear link between rooting and wild boar density. We performed six-year intensive spring-summer surveys (763 sampling plots; 3343 surveys between 2019–2024) in 9 protected areas of central Italy encompassing heterogeneous habitats and a gradient in wild boar densities, to investigate spatial variations in wild boar rooting and relevant drivers. Strong support was obtained for a positive relationship between rooting, at both large (i.e., study area) and fine (i.e., sampling plot) scales, and wild boar density in the area. Results supported lower rooting with increasing landscape diversity. Rooting was affected by topography, being reduced by rock cover and terrain steepness, and increased with distance from the nearest road/railway. Models of fine-scale rooting variation were elaborated to develop high-resolution (10 × 10 m) predictive maps of rooting impact, providing a tool scalable to ecologically comparable areas. Findings support the control of wild boar population density and maintenance of high landscape diversity as measures to reduce wild boar impacts. Finally, the present study also supports that rooting can serve as an effective indicator of within- and between-area variations in wild boar density.